Simultaneous determination of moisture and oil contents in palm fruits by near infrared spectroscopy - Omar, Muhammad Nor; Chik, Abu Bakar (Malaysian Agricultural Research and Development Institute, 1998)
Near infrared spectroscopic (NIRS) technique was assessed for rapid and simultaneous determination of moisture and oil contents in palm fruits. The sliced mesocarps were frozen and ground prior to analyses by wet chemistry and NIRS. Calibrations with 44 samples were developed for moisture and oil content respectively. Results showed that standard deviation (SD) for moisture content was 0.788 and multiple correlation coefficient (R) was 0.96. whereas those for oil content were 0.277 and 0.97 respectively. Prediction of moisture content with 10 samples showed that the standard error of prediction (SEP) was 0.382 and R was 0.97, whereas for oil content the SEP was 0.294 and R was 0.96.